Coincidence of virulence shifts and population genetic changes of Pseudoperonospora cubensis in the Czech Republic. (10th April 2015) - Kitner, M.; Lebeda, A.; Sharma, R.; Runge, F.; Dvořák, P.; Tahir, A.; Choi, Y.‐J.; Sedláková, B.; Thines, M.
Abstract : Pseudoperonospora cubensis is an oomycete pathogen causing downy mildew disease on a variety of Cucurbitaceae, and has recently re‐emerged as a destructive disease on crops in this family, mainly on cucumber and squash. Multilocus sequence analysis (MLSA) of four mitochondrial and two nuclear DNA regions was used to detect changes in the genetic structure of P. cubensis populations occurring in the Czech Republic that might be associated with recently reported shifts in virulence. The analysed sample set contains 67 P. cubensis isolates collected from 1995 to 2012 in the Czech Republic and some other European countries. Sequence analyses revealed differences and changes in the genetic backgrounds of P. cubensis isolates. While all isolates sampled before 2009 exhibited the genotype of the subspecies of Clade II and were collected from cucumber, all samples collected from other hosts belonged to Clade I ( P. cubensis sensu stricto ) or were sampled from 2009 onwards. In addition, 67·16% of all post‐2009 isolates from Clade II had two heterozygous positions in their nrITS sequence, which suggests sexual reproduction and/or a mutational origin. Thus, the results indicate that, apart from the rise in prevalence of Clade I, the change in the genetic structure of P. cubensis populations may be linked with a hybridization or, less likely, a mutation event that rendered strains able to infect a broader spectrum of host species.